Drivers of plant invasion vary globally: evidence from pine invasions within six ecoregions - Kimberley T. Taylor; Bruce D. Maxwell; Aníbal Pauchard; Martin A. Nuñez; Duane A. Peltzer; André Terwei; Lisa J. Rew (Global Ecology and Biogeography, 2016)
Aim To determine biotic and abiotic controls on pine invasion globally within six ecoregions that include both introduced and native ranges. Locations R ío N egro province, A rgentina; A ysén and A raucanía regions, C hile; S outh I sland (two ecoregions), N ew Z ealand; G reater Y ellowstone ecosystem, USA . Methods We quantified tree abundance and size across invasion fronts of the widespread invasive tree species P inus contorta at each of the nine sites, encompassing both the native and introduced range. We also determined the relative importance of propagule pressure, abiotic characteristics and biotic factors for invasion success. Finally, key plant population metrics such as individual tree growth rates and reproductive effort were compared between native and introduced ranges. Results P inus contorta density decreased with increasing distance from source population in all cases, but the importance and shape of this relationship differed among sites due, primarily to biotic factors. For example, areas dominated by native southern beech forest ( F uscospora cliffortioides or N othofagus spp.) were not invaded, and this biotic resistance was not overcome by high propagule pressure. In contrast, shrublands were more highly invaded than grasslands, contradicting previous generalizations about pine invasions. P inus contorta growth was faster, age to maturity was earlier and reproductive effort was higher in the introduced ranges compared with the native range, suggesting a demographic shift towards more rapid population growth in introduced regions. Climatic differences between the ranges may explain, at least in part, the observed pattern. Main conclusions We demonstrate that although biological invasions are driven by propagule pressure across different ecoregions, these processes interact strongly with biotic factors. Intriguingly, our results suggest that propagule pressure may become less important than biotic interactions as invasions proceed. Multi‐region studies including both the native and introduced ranges provide unparalleled opportunities for understanding how these interactions change among regions as invasions proceed.